ChemInform Abstract: Cobalt‐Catalyzed Cyclization of Carbon Monoxide, Imine, and Epoxide. Issue 41 (7th October 2014) - Zhang, Yubo; Ji, Jiamin; Zhang, Xiuliang; Lin, Shaohui; Pan, Qinmin; Jia, Li
Abstract gives access to substituted 1, 3‐oxazinan‐4‐ones derivatives